A compact uniplanar ultra‐wideband frequency selective surface for antenna gain improvement and ground penetrating radar application. Issue 10 (1st August 2020) - Kundu, Surajit
Abstract: A simple structured single layered frequency selective surface (FSS) that has unit cell size of 11 × 11 mm 2, substrate thickness of 0.8 mm only and capable to work in a very widespread band from 0.001 to more than 17 GHz is proposed in this article. The FSS is competent to augment the gain of a UWB monopole antenna by 2 to 3.5 dBi when integrated at the back of antenna. The performances of "antenna‐FSS" structure is evaluated by simulation and experimental measurement where good correlations are obtained. The integrated structure provides wide impedance band ( S 11 < −10 dB) from 2.82 to 19.94 GHz (more than 150%) with improved broadside radiation and high radiation efficiency profile. The transient and frequency domain characteristics of "antenna‐FSS" composite structure are also evaluated in close proximity of diverse sub‐surfaces such as dry sand, wet sand, wood and concrete where an almost unaltered impedance band profile, linear transfer function response and non‐varying group delay responses are achieved which establishes the applicability of the composite structure in ground penetrating radar for low depth sub‐surface scanning applications.